Aflatoxin B1 Binding by Lactic Acid Bacteria in Protein-Rich Plant Material Fermentation - Rämö, Sari; Kahala, Minna; Joutsjoki, Vesa (MDPI AG, 2022)
At the same time as the strong ambition to improve sustainability and the healthiness of food systems through a transition towards a more plant-based diet, climate change is increasing the risk of plant diseases. Consequently, mycotoxigenic fungi have become a food safety issue of major importance. A variety of strategies to suppress fungal growth in the pre- and postharvest stages of plant production have been established, and the potential of various biological methods has been assessed to ensure food safety. Of the various food microbes, lactic acid bacteria are known for their capacity to suppress the growth of toxigenic fungi and adsorb free mycotoxins. The current study showed that lactic acid fermentation could mitigate aflatoxin risk in plant-based foods through a reduction in free aflatoxin B1. In line with previous studies, in which Lactiplantibacillus plantarum (formerly Lactobacillus plantarum) was shown to reduce the level of free aflatoxin B1 in vitro, L. plantarum was shown to achieve up to a 90% reduction in free aflatoxin B1 in food fermentation. The results showed that traditional lactic acid fermentation, using L. plantarum as the starter strain, could be applied to mitigate aflatoxin B1 contamination risk in proteinaceous plant-based foodstuffs. In a wider context, fermentation using selected strains of lactic acid bacteria as starters could also enhance the availability of nutritious and safer food in terms of mycotoxin risk in low-income countries.
Keywords: aflatoxins; fermentation (metabolism); food safety; mycotoxin; aflatoxin B1; lactic acid bacteria